2020
DOI: 10.1101/2020.10.09.333351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of signaling pathways, matrix-digestion enzymes, and motility components controllingVibrio choleraebiofilm dispersal

Abstract: Bacteria alternate between being free-swimming and existing as members of sessile multicellular communities called biofilms. The biofilm lifecycle occurs in three stages: cell attachment, biofilm maturation, and biofilm dispersal. Vibrio cholerae biofilms are hyper-infectious and biofilm formation and dispersal are considered central to disease transmission. While biofilm formation is well-studied, almost nothing is known about biofilm dispersal. Here, we conduct an imaging screen for V. cholerae mutants that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 45 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…In summary, four signaling pathways have now been defined that feed into the regulation of V. cholerae biofilm dispersal: starvation (RpoS) (Singh et al, 2017), quorum sensing (via CAI-1 and AI-2) (Bridges and Bassler, 2019;Singh et al, 2017), the recently identified DbfS/DbfR cascade (ligand unknown) (Bridges et al, 2020), and through the current work, polyamine signaling via NpsS-MbaA. We propose that integrating the information contained in these different stimuli into the control of biofilm dispersal endows V. cholerae with the ability to successfully evaluate multiple features of its fluctuating environment prior to committing to the launch of this key lifestyle transition that, ultimately, impinges on its overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In summary, four signaling pathways have now been defined that feed into the regulation of V. cholerae biofilm dispersal: starvation (RpoS) (Singh et al, 2017), quorum sensing (via CAI-1 and AI-2) (Bridges and Bassler, 2019;Singh et al, 2017), the recently identified DbfS/DbfR cascade (ligand unknown) (Bridges et al, 2020), and through the current work, polyamine signaling via NpsS-MbaA. We propose that integrating the information contained in these different stimuli into the control of biofilm dispersal endows V. cholerae with the ability to successfully evaluate multiple features of its fluctuating environment prior to committing to the launch of this key lifestyle transition that, ultimately, impinges on its overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The biofilm lifecycle was measured using time-lapse microscopy as described previously (Bridges and Bassler, 2019). All plots were generated using ggplot2 in R. Light production driven by the vpsL promoter was monitored as described previously (Bridges et al, 2020). Results from replicates were averaged and plotted using ggplot2 in R.…”
Section: Bacterial Strains Reagents and Imaging Assaysmentioning
confidence: 99%
See 3 more Smart Citations